2014
DOI: 10.1111/ajt.12574
|View full text |Cite
|
Sign up to set email alerts
|

The Allo- and Viral-Specific Immunosuppressive Effect of Belatacept, but Not Tacrolimus, Attenuates With Progressive T Cell Maturation

Abstract: Tacrolimus impairs allo- and viral-specific T cell responses. Belatacept, a costimulation-based alterative to tacrolimus, has emerged with a paradoxical picture of less complete control of alloimmunity with concomitant impaired viral immunity limited to viral-naïve patients. To reconcile these signatures, bulk population and purified memory and naïve lymphocytes from Cytomegalovirus (CMV) seropositive (n=10) and seronegative (n=10) volunteers were studied using flow cytometry, interrogating proliferation (CFSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 23 publications
(24 reference statements)
1
72
1
Order By: Relevance
“…However, this was not the case using an antagonist of CD80/86 (CTLA4-Ig), which inhibits similarly naive and memory T cell proliferation stimulated with alloantigens but not when stimulated with viral peptides. This is in accordance with a recent study reporting that CTLA4-Ig efficiency decreased in increasingly matured human T cells when stimulated with a CMV peptide or alloantigens (30). Collectively, our results suggest that human memory T cell reactivation in vitro is still CD28-dependent but tightly controlled by CTLA-4 and/or PD-L1 coinhibitory signals as described in mouse models of candida or Listeria monocytogenes infection (31,32).…”
Section: Discussionsupporting
confidence: 93%
“…However, this was not the case using an antagonist of CD80/86 (CTLA4-Ig), which inhibits similarly naive and memory T cell proliferation stimulated with alloantigens but not when stimulated with viral peptides. This is in accordance with a recent study reporting that CTLA4-Ig efficiency decreased in increasingly matured human T cells when stimulated with a CMV peptide or alloantigens (30). Collectively, our results suggest that human memory T cell reactivation in vitro is still CD28-dependent but tightly controlled by CTLA-4 and/or PD-L1 coinhibitory signals as described in mouse models of candida or Listeria monocytogenes infection (31,32).…”
Section: Discussionsupporting
confidence: 93%
“…However, following depletion we observed a dramatic shift of expression from memory to naïve that persisted throughout reconstitution. Furthermore, these repopulating naïve cells expressed CD28 and therefore were susceptible to costimulation blockade (8, 10) , supporting this as a mechanism for the efficacy of this regimen. Practically, this introduces a method to formally assess the dynamic period of post-depletional repopulation, and we would suggest that Ki67 measurement be considered as a mechanistic adjunct to studies involving vigorous induction therapy, particularly when subsequent immunosuppressive minimization is concerned.…”
Section: Discussionmentioning
confidence: 94%
“…PBMCs were stimulated with CD3-depleted PBMCs from either the original kidney donors, HLA-mismatched third-party allo-donors, CMV-pp65 peptides, or EBV proteins and interrogated by intracellular cytokine staining (ICCS). Previous studies have demonstrated that multi-cytokine producing T cells respond more vigorously to specific antigens when compared with single-cytokine producers (8, 10, 31-32) . We therefore applied the definition of a TNF-α/IFN-γ/IL-2 triple cytokine producing T cell as a significant responder to antigen stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been recently shown that belatacept’s immunosuppressive effect, in contrast to that of tacrolimus, weakens with increasingly matured effector cells. 4 Although costimulation blockade-based immunotherapies boast superior side effect profiles compared to calcineurin inhibitor-based therapies, 3 overcoming the CoBRR hurdle is critical to their generalized use. This review will focus on CD28 loss in humans unless otherwise noted.…”
Section: Introductionmentioning
confidence: 99%